C33 PERCUTANEOUS CLOSURE OF MITRAL PARAVALVULAR LEAK (PVL): WHEN REVERSAL MAKES ALL THE DIFFERENCE. (18th May 2022) - Manca, F; Cocco, D; Siotto, P; Melis, M; Fele, G; Corda, M; Loi, B
Abstract: PVL is a complication associated with the implantation of a prosthetic valve. Since surgical re–intervention has a high operative risk, percutaneous closure (PC) has emerged due to its reduced invasiveness and the development of dedicated materials. We describe the case of a 66–year–old man with a mechanical oscillating disc mitral prosthesis who was admitted for acute heart failure. An echo showed a left ventricle with normal motion and a postero–medial mitral PVL with significant regurgitation. A transoesophageal echo confirmed the PVL in the 5 o'clock viewing portal with severe regurgitation. After optimising the medical therapy and with no change in echo findings, a cardiac catheterisation showed persistent post–capillary pulmonary hypertension, and therefore PC of the PVL was scheduled. Given the postero–medial location of the PVL, a transseptal puncture was performed using a 8.5 Fr Agilis introducer (Terumo) with telescoping system of a 6 r. JR4 catheter. The PVL was passed through with a Terumo 0.035 J–shaped guide, but without managing to advance the catheter beyond the leak. The guide was therefore advanced into the abdominal aorta and an arteriovenous circuit was created, which allowed the catheter to be advanced beyond the PVL and a closure device (AVPIII 14/5, Abbott St.Jude) was positioned with anterograde placement, with a distal disc on the ventricular side. Obliteration of the PVL, interference with the prosthetic disc and high transprosthetic gradients were observed despite several attempts to relocate the AVP, which was therefore removed. A second procedure was performed at a distance, creating a similar arteriovenous circuit by using a long introducer (110cm–Cook) which was advanced from the femoral artery beyond the leak in the opposite direction. An AVPIII (12/5) with a distal disc on the atrial side was positioned, this time with retrograde placement, with effective closure of the PVL and minimal residual regurgitation, without interference with the prosthesis. The course was free of complications; after one month the echo confirmed the result. Transcatheter closure of the PVL is a complex procedure, but relatively safe in experienced hands. This case is of particular interest due to the difficulty presented by the location of the PVL, which required measures of high technical complexity and because it describes a possible complication of the procedure, which was resolved by the simple reversal of the placement of the device.